The reproductive biology and conservation of rare orchid species in Ireland - Duffy, Karl Joseph (Trinity College (Dublin, Ireland). Department of Botany, 2008)
This thesis investigates the factors that affect the conservation and reproductive biology of rare Irish orchids. Research focused on various aspects of the ecology of six species that occur throughout Ireland. Four endangered, red-listed species were examined; Cephalanthera longifolia, Hammarbya paludosa, Pseudorchis albida, and Spiranthes romanzoffiana. In addition, one rare species Neotinea maculata and one relatively abundant species Spiranthes spiralis were also examined. I employed probabilistic models to infer threat of four species (C. longifolia, H. paludosa, N. maculata, and P. albida).
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin